Epidemiological and Antimicrobial Resistant Patterns, and Molecular Mechanisms of Carbapenem-Resistant Klebsiella pneumoniae Infections in ICU Patients - Lu F; Zhang L; Ji J; Xu Y; Wang B; Xia J (Infection and Drug Resistance, 2023)
Fanbo Lu,1,* Luwen Zhang,1,* Juanjuan Ji,2 Yuanhong Xu,1 Bo Wang,1 Jinxing Xia1 1Department of Clinical Laboratory, First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, First Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinxing Xia; Bo Wang, Department of Clinical Laboratory, First Affiliated Hospital of Anhui Medical University, No. 218 Jixi Road, Hefei, Anhui, People’s Republic of China, Email xiajinxing@ahmu.edu.cn; wangbo8711@126.comObjective: To study the epidemiological and antimicrobial resistant patterns, clinical characteristics and risk factors of critically ill patients infected with carbapenem-resistant Klebsiella pneumoniae (CRKP) from intensive care units (ICUs). The potential molecular mechanisms of antimicrobial resistance and virulence of CRKP were investigated through evaluation of associated genes.Methods: Totally, 201 ICU patients infected with K. pneumoniae were recruited from January 2020 through January 2021. K. pneumoniae strains were collected from diverse clinical specimens and identified by microbial cultures and matrix-assisted laser desorption ionization–time-of-flight mass spectrometry. Antimicrobial resistance was measured through broth micro-dilution or Kirby–Bauer assays. The carbapenemase-, virulence-, and capsular serotype-associated genes of CRKP were individually detected by PCR and sequencing. Demographic and clinical profiles were acquired from hospital databases to evaluate the correlation of CRKP infection incidence with clinical risk factors.Results: Of the 201 K. pneumoniae strains, CRKP accounted for 41.29%. Seasonal bias existed in local prevalence of CRKP infections. CRKP strains mounted significantly strong resistance against major antimicrobial agents except ceftazidime–avibactam, tigecycline and minocycline. Recent exposure to certain antibiotics and prior treatment with invasive interventions were prone to increase CRKP infection risks with worsened infectious outcomes. The local top carbapenemase-encoding and virulence-associated genes of CRKP were blaKPC and irp 2, respectively. Nearly half of CRKP isolates harbored a capsular polysaccharide serotype of K14.K64 (wzi-64) which preferentially emerged in the cohort with worse outcomes of infection.Conclusion: Featured epidemiology and typical clinical characteristics existed extensively in K. pneumoniae infections among ICU patients. The CRKP cohort exhibited substantially high antimicrobial resistance. Distinctive carbapenemase-, virulence-, and serotype-associated genes were intensively involved in the spread and pathogenesis of CRKP. These findings supported careful management of critically ill patients potentially infected with virulent CRKP in the ICUs.Keywords: carbapenem-resistantKlebsiella pneumoniae, epidemiology, clinical features, antimicrobial resistance, virulence, ICU